Embossed Template Induced Particles Assembly for Heterostructures and the Application in High‐Security Encryption. (4th December 2022) - Guo, Dan; Ruan, Jun; Xu, Yanan; Li, Kaixuan; Han, Yu; Guo, Jinxin; Zhang, Xinping; Li, Yixuan; Ge, Kun; Zhai, Tianrui; Song, Yanlin
Abstract: The coassembly of primary particles into heterostructures represents a significant strategy for advanced fabrication of multi‐functional materials or devices, and templated assembly has shown remarkable advantage for deterministic placement of particles and the efficient integration with substrates. However, template induced particles coassembly, which is significant for integrating multicomponents at desired positions, is still challenging. Herein, a facile strategy of embossed templateinduced particles coassembly for diverse superstructures and precise patterns is reported. Tunable region selective assembly of particles is demonstrated by controlling the resistance force via designing the embossed edge and surface roughness of the template. Through regulating the template morphologies and particles composition, well‐controlled coassembly of "flower" shaped heterostructure and chiral superstructure arrays are realized. Furthermore, the printable nanomaterials self‐assembly template is employed to achieve totally bottom‐up fabrication of excitation responsive heterostructure arrays, in which the multi‐photons process based energy transfer is studied to show the application in high‐secure encryption. With the advantage of accurate position and compatible to different materials, this strategy is expected to provide a promising platform for fabricating micro/nanoscale advanced devices. Abstract : A facile strategy of embossed template‐induced particles coassembly for diverse superstructures and precise patterns is reported. Through tuning the template morphologies and particles composition, we achieve well‐controlled coassembly of "flower" shaped heterostructure, chiral superstructure, and totally bottom‐up fabrication of excitation responsive heterostructure arrays with the application in high‐secure encryption.